CONTROL OF FRAGMENTATION BY BLASTING - Branko Božić (Rudarsko-geološko-naftni Zbornik, 1998)
The degree of fragmentation influences the economy of the excavation operations. Characteristics of blasted rock such as fragment size, volume and mass are fundamental variables effecting the economics of a mining operation and are in effect the basis for evaluating the quality of a blast. The properties of fragmentation, such as size and shape, are very important information for the optimization of production. Three factors control the fragment size distribution: the rock structure, the quantity of explosive and its distribution within the rock mass. Over the last decade there have been considerable advances in our ability to measure and analyze blasting performance. These can now be combined with the continuing growth in computing power to develop a more effective description of rock fragmentation for use by future blasting practitioners. The paper describes a view of the fragmentation problem by blasting and the need for a new generation of engineering tools to guide the design and implementation of blasting operations.